Quality of Life for Hypertension Patients Receiving Medication Therapy With Amlodipine At The Bara-Baraya Health Center - Leony Agnes Deysiana (Saintify Publish, 2024)
Quality of life (Quality of Life) is an individual assessment relating to the health conditions that are being experienced to assess the impact of a therapy performed on patients with chronic diseases. Measurement of quality of life carried out in hypertensive patients is to examine the types of hypertension drugs consumed by hypertensive patients. Hypertension is a non-communicable disease that can reduce the quality of life because it requires regular treatment and takes a long time. The most commonly used drug for hypertension is Amlodipine. The aim of this study was to determine the quality of life of hypertensive patients with Amlodipine drug therapy at the Bara-baraya Health Center, Makassar City. The sampling technique used was Total Sampling and 14 respondents were found according to the quality of life criteria and data collection used the SF-30 questionnaire. The results of the study were carried out descriptively by determining the percentage of good and bad categories. The domain of physical function is in the good category, namely 12 people (85.7%), physical limitations are in the bad category, namely 12 people (85.7%), body pain is in the bad category, namely 8 people (57.2%), general health is in the bad category, namely 9 people (64.3%), vitality is in the good category, namely 10 people (71.4%), social function is in the bad category, namely 10 people (71.4%), emotional limitations are in the good category, namely 9 people (64.3%), and mental health is in the good category, namely 9 people (64.3%). The conclusion from the results of this study showed that the level of quality of life of hypertensive patients with Amlodipine drug therapy at the Bara-baraya Health Center in Makassar City was 50% with a poor quality of life category.